The Automatic Detection of Power Theft and Excessive Power Usage in Libyan Electricity Network (European Journal of Engineering Science and Technology, 2019)
The General Electric Company Of Libya (GECOL) suffers from a power theft phenomenon which is considered as one of the main causes that lead to the load shading problems. This work proposes a system that provides a solution to this problem. Power theft occurs mainly by premises that require high power consumption like houses, factories, and farms. The system automatically detects the illegal users by placing a current sensor on an energy meter that supplies a certain area with electricity. The sensor will assist in the distinction of illegal consumption. It will be connected to the Arduino to compare the sensed value that represents the actual consumption with the specified consumption value set by GECOL which is stored in the Microcontroller memory. The Arduino is interfaced between the energy meter, current sensor, voltage sensor, and relay. The proposed model is simulated by Proteus as the 1 KW distribution line with three loads. Power system output checks continuously the status of the user connection and displays which line got power theft. Once power theft detected the system is cutting the user connection using a relay as a punishment. Then the system is enabling the user connection again. The system can also send a notification message to inform GECOL that there is an additional unexpected consumption detected in that particular energy meter. As a result, GECOL can ensure weather this detected power is authorized by the company.